Захист інтелектуальної власності тих, хто навчається, у системі освіти - Ізбаш, Олеся Олегівна; Избаш, Олеся Олеговна; Izbash, Olesja (Одеса : Юрид. л-ра, 2014)
Article is devoted to highlighting the problems of the protection of intellectual property of the learners (pupils, students) in the process of education. Intellectual property is examined as a major resource of institute of higher, which maybe and must become the real factor him economic development as main source of fundamental and applied knowledges which are underlaid scientific developments and researches.
Ізбаш О. О. Захист інтелектуальної власності тих, хто навчається, у системі освіти / О. О. Ізбаш // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.) Ю. П. Аленін [та ін.] ; МОН України; НУ ОЮА. – Одеса : Юрид. л-ра, 2014. – Вип. 74. – С. 256-262.
Keywords: інтелектуальна власність; студенти; ВНЗ; интеллектуальная собственность; студенты; ВУЗ; intellectual propertу; students; university